El cierre de las escuelas comunitarias y su incidencia en el proceso educativo : análisis de caso en la comunidad Guantug, parroquia Chugchilán - Pilatasig Pilatasig, María Encarnación (2018)
This research project studies the closure of community schools and their impact on the educational process. It was carried out with the purpose of knowing the causes that generated this process, as well as the impact it caused in the community. The case study was carried out in the closed school San José de Guantug located in the community of Guantug parish, Chugchilán, canton Sigchos in the province of Cotopaxi. The work is based on an investigation that starts from the review of educational policies and the contributions of some authors on the subject in question. The purpose of the theoretical inquiry is precisely to establish the relevant foundation that provides a conceptual framework for field research. Regarding the methodological scope, the work was based on the inductive method and for data collection we used a series of previously constructed instruments that were aimed at authorities, parents, teachers and children involved in the closure process from school. The analysis of the results was carried out qualitatively and quantitatively with the design of the respective tables and their interpretation. From the theoretical development, the field work and the analysis of results, we proceeded with the formulation of some conclusions and recommendations that gather the most important findings and learnings.